Targeting METTL3 mitigates venetoclax resistance via proteasome-mediated modulation of MCL1 in acute myeloid leukemia - Chang-qing Jiao; Chen Hu; Meng-hua Sun; Yan Li; Chao Wu; Fei Xu; Lei Zhang; Fu-rong Huang; Jun-jie Zhou; Ji-fei Dai; Min Ruan; Wen-chao Wang; et al. (Cell Death and Disease)
Abstract Venetoclax, a selective BCL2 inhibitor, is extensively utilized in clinical settings for the treatment of acute myeloid leukemia (AML). However, its efficacy is often compromised by the development of drug resistance. Hence, identification of potential venetoclax combination treatment strategies is imperative to overcome this acquired resistance. In this study, we discovered that inhibition of METTL3 can synergistically enhance the anti-leukemic efficacy of venetoclax, and is capable of overcoming venetoclax resistance in in vivo experiments and various venetoclax resistance models. Mechanistic study revealed that STM2457 augmented venetoclax activity by downregulating MCL1 and MYC, thereby increasing apoptosis in leukemia cells induced by venetoclax. Further investigation demonstrated that STM2457 promotes the ubiquitination and subsequent protein degradation of MCL1 primarily through pharmaceutically targeting METTL3. Moreover, through molecular docking-based virtual screening, we identified isoliquiritigenin as a potential novel small molecule natural product targeting METTL3, which exhibited potential effects as an anti-leukemic agent.